2000
DOI: 10.1161/01.hyp.35.2.621
|View full text |Cite
|
Sign up to set email alerts
|

Amlodipine, Enalapril, and Dependent Leg Edema in Essential Hypertension

Abstract: Abstract-Calcium channel blockers (CCBs) blunt postural skin vasoconstriction, an autoregulatory mechanism that minimizes gravitational increases in capillary pressure and avoids fluid extravasation when standing. To evaluate the dose-response relation between this pharmacological interference and dependent edema, a frequent side effect of CCBs during antihypertensive treatment, skin blood flow (laser Doppler flowmetry) at the dorsum of the foot, both supine and with the limb passively placed 50 cm below the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 27 publications
3
40
0
1
Order By: Relevance
“…13,14 The mechanisms by Valsartan-amlodipine combination and ankle oedema R Fogari et al which ARB may attenuate the CCB-induced oedema are not clear but possibly resemble those hypothesized for ACE-I. [4][5][6][7][8] Thus, RAAS blockade by both ACE-I and ARB is likely to result in venous capacitance vessels vasodilation with consequent intracapillary pressure normalization and reduced fluid exudation from the intracapillary space into the interstitium. The ability to affect the vasodilatory mechanism of the oedema produced by CCB seems to make not only ACE-I but also ARBs able to alleviate this side effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 The mechanisms by Valsartan-amlodipine combination and ankle oedema R Fogari et al which ARB may attenuate the CCB-induced oedema are not clear but possibly resemble those hypothesized for ACE-I. [4][5][6][7][8] Thus, RAAS blockade by both ACE-I and ARB is likely to result in venous capacitance vessels vasodilation with consequent intracapillary pressure normalization and reduced fluid exudation from the intracapillary space into the interstitium. The ability to affect the vasodilatory mechanism of the oedema produced by CCB seems to make not only ACE-I but also ARBs able to alleviate this side effect.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The mechanisms underlying CCB-induced oedema, although not completely understood, possibly include: (a) an increase in capillary hydrostatic pressure, with consequent transcapillary fluid loss, that results from a relatively more pronounced vasodilation in precapillary than postcapillary resistance vessels; 4-6 (b) an interference with the local vascular control, probably the myogenic component, that operates to protect dependent vascular regions from increased fluid filtration. [7][8] With any form of oedema, most physicians add a diuretic to the antihypertensive treatment. Unfortunately, diuretics, either loop or thiazide, have little effect on CCB-induced oedema because they merely decrease fluid retention but do not affect the vasodilatory mechanism of the oedema, which is predominant with CCB.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Although the precise mechanisms causing the Ca-antagonist-induced oedema are still not completely understood, the most likely reason appears to be an increase in capillary hydrostatic pressure with consequent transcapillary fluid loss that results from a relatively more pronounced vasodilation in precapillary than postcapillary resistance vessels. [12][13][14] It has also been suggested that the Ca-antagonist-related oedema could be partly ascribed to interference by these drugs with the local vascular control (probably the myogenic component) that operates to protect dependent vascular regions from increased fluid filtration, 15,16 whereas sodium retention and activation of the renin-angiotensin system seem to play a minor role. 14,17 Most reports about the lower incidence of Caantagonist-induced ankle oedema with the addition of an ACE-I are generally based on a simple collection of reported side effects, that is, on subjective parameters rather than objective estimates of the magnitude of this effect.…”
Section: Introductionmentioning
confidence: 99%
“…1 The maximum recommended dose of amlodipine, which is not uncommonly associated with pedal edema, often is required to control BP in black patients. 20 Equivalent BP lowering and better tolerability with valsartan/HCTZ compared with amlodipine would support use of this combination as an alternate, first-line therapy in blacks with hypertension.…”
mentioning
confidence: 99%